2023
DOI: 10.1029/2022wr032864
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Dynamics and Bed Stability in Step‐Pool Streams: Insights From 18 Years of Field Observations

Abstract: Step‐pools are a common morphology in gravel‐bed streams with gradients between 3% and 30%, where coarse sediment and wood are present. Recent experimental work has offered insight on the formation of step‐pools, flow resistance, and interactions between sediment transport and channel morphology. However, field observations are sparse and often limited by short observation periods. Using an extensive 18‐year data set, we examine controls on sediment mobility, step stability, and sediment storage in East Creek,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
(121 reference statements)
0
4
0
Order By: Relevance
“…In another field study, researchers considered a reach of Babolroud river with width variation and found that the vertical components of the velocity near the pool bed are oriented downward, and upwards near the water surface, while in the riffle part, these components are oriented towards the bed in gravel-bed rivers, emphasizing the effect of width changes, flow non-uniformity, and changes in input sediments on the morphodynamics of the pool-riffle sequence [21]. Hassan et al (2023) [22] determined the sediment mobility, step stability, and sediment storage in a step-pool reach in British Columbia in Canada. They revealed that sediment mobility is not dependent on the flow magnitude but is controlled by sediment supply [22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another field study, researchers considered a reach of Babolroud river with width variation and found that the vertical components of the velocity near the pool bed are oriented downward, and upwards near the water surface, while in the riffle part, these components are oriented towards the bed in gravel-bed rivers, emphasizing the effect of width changes, flow non-uniformity, and changes in input sediments on the morphodynamics of the pool-riffle sequence [21]. Hassan et al (2023) [22] determined the sediment mobility, step stability, and sediment storage in a step-pool reach in British Columbia in Canada. They revealed that sediment mobility is not dependent on the flow magnitude but is controlled by sediment supply [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hassan et al (2023) [22] determined the sediment mobility, step stability, and sediment storage in a step-pool reach in British Columbia in Canada. They revealed that sediment mobility is not dependent on the flow magnitude but is controlled by sediment supply [22]. Based on their research, the amount of width and wavelength change were known as significant factors affecting the sequence of pools and riffles.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of bedload measurement procedures in East Creek can be found in Hassan, Saletti, et al. (2022). Because collecting bedload samples was not always possible after each flow event due to weather conditions, only GSDs that were associated to single events were used for comparison with simulated bedload GSDs.…”
Section: Methodsmentioning
confidence: 99%
“…Though many authors have studied sediment transport processes and bed stability in East Creek (Cienciala & Hassan, 2013; Hassan et al., 2021, 2022b, 2022c; McDowell et al., 2021; McDowell & Hassan, 2020; Papangelakis & Hassan, 2016; Wlodarczyk et al., 2023), this study is the first to use a sediment transport model that accounts for spatial variations in fractional sediment mobility.…”
Section: Introductionmentioning
confidence: 99%